Nanocrosses with Highly Tunable Double Resonances for Near-Infrared Surface-Enhanced Raman Scattering. (25th February 2012) - Jian, Ye; Pol, VanDorpe
Abstract : We present asymmetric gold nanocrosses with highly tunable double resonances for the near-infrared (NIR) surface-enhanced Raman scattering (SERS), optimizing electric field enhancement at both the excitation and Stokes Raman wavelengths. The calculated largest SERS enhancement factor can reach a value as large as 1.0 × 10 10 . We have found that the peak separation, the resonance position, and peak intensity ratio of the double-resonance gold nanocrosses can be tuned by changing the structural dimensions or the light polarization.